SYNCHRONIZATION OF CUSTOMARY LAW AND NATIONAL LAW: THE PERSPECTIVE OF THE NORTH TORAJA PEOPLE - Samaluddin, Samaluddin; Nasrin, Nasrin; Wiridin, Darmawan (LPPM STIH Putri Maharaja, 2024)
Customary law has become an important part of the life of the people of North Toraja, its existence in solving social problems that occur is evidence that its role is very strategic. This research aims to understand how the people of North Toraja view and adapt customary law in the context of national law. Along with the challenges of globalization and social change, a deep understanding of the synchronization of these laws is very important. In this study, researchers used a case study research method with an explanatory research approach. The subjects in this study amounted to 3 (three) people consisting of traditional leaders, community leaders and local government. Based on the results of this study, it shows that synchronization between customary law and national law in North Toraja is a strategic step to create a more comprehensive and effective legal system for the needs of society. By integrating local values into the national legal framework, it is expected to build a harmonious and respectful society between tradition and modernity. The synchronization of customary law and national law in North Toraja shows that the integration of these two legal systems is essential to create justice and sustainability in society.